Bright future of deep-ultraviolet photonics: emerging UVC chip-scale light-source technology platforms, benchmarking, challenges, and outlook for UV disinfection - Sharma, Vijay Kumar (2022)
The COVID-19 pandemic has generated great interest in ultraviolet (UV) disinfection, particularly for air disinfection. Although UV disinfection was discovered close to 90 years ago, only very recently has it reached the consumer market and achieved much acceptance from the public, starting in the 2000s. The current UV light source of choice has been almost exclusively a low-pressure mercury vapor discharge lamp. Today, however, with emerging deep-UV (DUV) chip-scale technologies, there has been a significant advancement, along with ever-increasing interest, in the development and deployment of disinfection systems that employ compact devices that emit in the deep-UV spectral band (200–280 nm), including UV light-emitting diodes (LEDs) and cathodoluminescent (CL) chips. This perspective looks into competing UV technologies (including mercury lamps and excimer lamps as benchmarks) on their optical merits and demerits and discusses the emerging chip-scale technologies of DUV electroluminescent and cathodoluminescent devices, comparing them against the benchmarks and providing an overview of the challenges and prospects. The accelerating progress in chip-scale solutions for deep-UV light sources promises a bright future in UV disinfection.